1985
DOI: 10.1002/aja.1001740107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1‐hydroxyethylidene‐1, 1‐bisphosphonate (HEBP) on the formation of dentin and the periodontal attachment apparatus in the mouse

Abstract: The effects of the bisphosphonate HEBP on dentin formation and the structural relationship between the dentin and the developing periodontal attachment apparatus have been studied in the continuously growing mouse incisor. It was observed that HEBP (in doses greater than or equal to 8 mg P/kg b.w/day) not only inhibited the deposition of mineral crystallites in newly formed dentin matrix, but also entirely prevented the formation of a layer of acellular root cementum. It was further noticed that the drug inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0
9

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 30 publications
10
30
0
9
Order By: Relevance
“…These findings further substantiate the notion that intrinsic differences exist in the rodent incisor between the ERD and CRD with respect to formation and mineralization of dentin (Beertsen et al, 1985;Beertsen and Niehof, 1986;Steinfort et al, 1989Steinfort et al, , 1990.…”
Section: Methodssupporting
confidence: 75%
“…These findings further substantiate the notion that intrinsic differences exist in the rodent incisor between the ERD and CRD with respect to formation and mineralization of dentin (Beertsen et al, 1985;Beertsen and Niehof, 1986;Steinfort et al, 1989Steinfort et al, , 1990.…”
Section: Methodssupporting
confidence: 75%
“…Thus, Beertsen and colleagues found differences in reactivity to bisphosphonate, in amino acid incorporation, as well as differences with respect to phosphoprotein distribution (Beertsen et al, 1985;Beertsen and Niehof, 1986;Steinfort et al, 1989). In bovine incisors, phosphoproteins, present in the crown, could not be detected in the root (Takagi et al, 1988).…”
Section: E Root Dentin Formationmentioning
confidence: 99%
“…Although several studies have suggested that bisphosphonates do not adversely affect the osteoblast activity (Sato et al 1991;Nii et al 1994;Rodan and Fleisch 1996;Evans 2002), cells other than osteoclasts may also be affected by bisphosphonates in other mineralized tissues. It has also been reported that bisphosphonates act as inhibitors of mineralization in bone (Francis 1969;King et al 1971;Schenk et al 1973) and tooth (Reynolds et al 1973;Beertsen et al 1985;Ogawa et al 1989;Takano et al 1998;Sakai et al 1999;Jayawardena et al 2002). Indeed, administration of bisphosphonates at high and successive doses has been shown to affect mineralization of both dentin and enamel (Simmelink 1987;Izumi 1989;Ohya et al 1989;Fejerskov et al 1990;Weile et al 1990Weile et al ,1993Fouda et al 1991;Wakamatsu 1991;Takano et al 1998).…”
Section: Introductionmentioning
confidence: 99%